Rekonstruksi Peran Apresiasi Dan Kritik Sastra Dalam Meningkatkan Mutu Karya: Tinjauan Kritis Atas Praktik Dan Teori - Dian Harahap; Eny Sihite; Lusinda Sigiro; Rotua Lumbantoruan; Talenta Sembiring; Yesika Simbolon (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This critically discusses the role of literary appreciation and criticism in enhancing the quality of literary works by thoroughly reviewing existing practices and theories. Through a qualitative analysis approach, this study highlights how appreciation and criticism not only function as passive responses to works but also as active instruments that shape the quality and innovation of literature. This paper recommends the reconstruction of a more integrated and reflective paradigm of literary appreciation and criticism to significantly contribute to the improvement of literary quality.